Analysis of the Influence of Price, Service Quality and Location on Purchasing Decisions of Honda Brand Motorcycles at PT Daya Motor Selaparang Mataram - Alqifari, Ma’ruf; Sulaeman, Sulaeman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research was conducted to find out how much influence price, service quality and location have on purchasing decisions for Honda brand motorbikes within PT Daya Motor Selaparang Mataram.The population used in this research were consumers who had purchased a Honda brand motorbike at PT Daya motor Selaparang, Mataram. The sample in this study consisted of 100 respondents and the technique used was a nonprobability sampling technique with an accidental sampling approach (sampling based on chance). From the results of the analysis, the indicators in this research are valid and valid variables. And the most dominant factor influencing purchasing decisions is the service quality variable with a regression coefficient of xx, then the price variable with a regression coefficient of xx and finally location with a regression coefficient of xx. The dependent variable in this research is quite good at explaining the independent variable (purchasing decisions). The author's suggestions are for motorbike things that have been assessed by consumers and correct things that are not good in the opinion of consumers.